User color temperature preferences in immersive virtual realities. (June 2019) - Siess, Andreas; Wölfel, Matthias
Highlights: There are differences in preferred color temperature between VR and PC screens. These differences are gender dependent. The daytime when VR is used has also an impact on the personal preferences. Seasonal perceptive differences may also influence the preferred color tints. Graphical abstract: Abstract: Virtual reality is currently experiencing a renaissance, with more and more fields of application emerging and more and more users spending an increasing amount of time using head mounted displays (HMD). While technical parameters such as field of view or pixel density are heavily researched, some fundamental aspects of perception and in particular the effects on human cognition and physical constitution are less investigated. One of these aspects to be addressed in this study is the perceived color temperature—a stimulus to which every color-seeing person reacts both consciously and subconsciously. A total of 86 test persons were asked to adjust the color temperature according to their personal taste in five photorealistic scenarios; once using a PC screen and once using a HMD. Between these two devices significant differences in the personal preferences of the test persons were found. This study will open a broad discussion about the effects of color temperature as an omnipresent stimulus and how external factors like daytime or season may effect these preferences in immersive environments.